Long-term follow-up of benign positional vertical opsoclonus in infants: retrospective cohort. Issue 6 (13th September 2017) - Sternfeld, Amir; Lobel, Daniella; Leiba, Hana; Luckman, Judith; Michowiz, Shalom; Goldenberg-Cohen, Nitza
Abstract : Background/Aims: Benign positional vertical opsoclonus in infants, also described as paroxysmal tonic downgaze, is an unsettling phenomenon that leads to extensive work-up, although benign course has been reported in sporadic cases. We describe long-term follow-up of a series of infants with the phenomenon. Methods: This retrospective cohort included all infants diagnosed with rapid downgaze eye movement in 2012–2015 and followed until 2016. The databases of two medical centres were retrospectively reviewed. Benign positional vertical opsoclonus was diagnosed based on clinical findings of experienced neuro-ophthalmologists. Data were collected on demographics, symptoms and signs, neuro-ophthalmological and neurological evaluations, and outcome. Imaging studies were reviewed. Main outcome measures were long-term outcome and findings of the thorough investigation. Results: The cohort included six infants. All infants were born at term. Age at presentation was several days to 12 weeks. Episodes lasted a few seconds and varied in frequency from <10 to dozens per day. In five infants, symptoms occurred in the supine position. There was a wide variability in the work-up without any pathological findings. Follow-up ranged from 1 to 2.5 years. Ocular symptoms gradually decreased until resolution. Infants reached normal developmental milestones. Conclusions: Our identification of six patients in only 3 years suggests benign positional vertical opsoclonus may be more prevalent than previously described. In our experience, it affects otherwise healthy infants and resolves spontaneously. In view of the good long-term outcome, a comprehensive clinical investigation may not be necessary.